A Physical Model Test of Coal-Mining-Induced Deformation Mechanisms in a Canal - Renwei Ding; Ye Tian; Handong Liu; Tong Jiang; Huaichang Yu; Dongdong Li (Applied Sciences)
The route of the South-to-North Water Diversion channel strides across part of the coal mine goaf in Yuzhou County, Henan Province, China, and long-term deformation due to coal seam recovery poses a threat to the safe operation of the main canal. Therefore, the study of the deformation mechanisms induced by coal seam recovery is of great significance to the canal’s safe operation, as well as to deformation monitoring and to the development of early warnings. The geologic model was established based on the geological engineering conditions of the Yuzhou Gongmao mining area, spanning the main canal of the South-to-North Water Diversion Project; then, the physical model test was carried out according to similar theories. The deformation characteristics of the rock overlay and the channel above the goaf were analyzed, and failure criteria for overburdened rock and the channel were proposed. The results showed that horizontal fissures were gradually observed in the overlying rock as the coal mining progressed, extending and widening. When the goaf was excavated to 76 cm, the overlying rock body suddenly collapsed as a whole, and the channel collapsed and was destroyed. During the formation of the goaf, there was a critical span ratio (R): When the height-to-span ratio was greater than 0.039, the collapse of overlying rock occurred only within a certain range above the goaf. When the height-to-span ratio was less than 0.039, the overlying rock body collapsed in a wide area, and the soil on both sides of the channel collapsed to the center of the channel, presenting a “V” glyph collapse. The sediment in the center of the channel measured 22 mm, and there were multiple tensile cracks on both sides of the embankment, with a width of 5–10 mm. The vertical deformation of the channel went through three stages, namely, the initial deformation stage, the deceleration deformation stage, and the stability stage. This study can provide scientific guidance for early warnings of channel deformation and safe operation across the goaf.